Fiscal Vulnerabilities in Commodity Exporting Countries and the Role of Fiscal Policy - Richaud, Christine (World Bank, Washington, DC, 2019)
The paper updates the analysis of the fiscal policy response over the recent commodity cycle, contributes to the analysis of key drivers of fiscal policy procyclicality, and provides a stock-tacking of current fiscal vulnerabilities. Countercyclical fiscal policy during good times has been a key factor affecting the ability of commodity exporters to sustainably support economic activity when prices started declining. Fiscal space to withstand the next shock has narrowed in many emerging and developing economies (EMDEs) and may also be constrained by contingent liabilities stemming from exposure of state-owned enterprises and public and systemic banks to the commodity-sector. Fiscal consolidation is still necessary in many commodity-exporting EMDEs to reduce debt risks, rebuild fiscal and external buffers, and facilitate access to affordable financing. Fiscal policy should particularly aim at reducing the high volatility of public investment spending in commodity-exporting countries, both in good and bad times.